Cross-sectional study on the dissociation of decision-making capacity for antipsychotic treatment and COVID-19 vaccination in individuals with schizophrenia - Raffard, Stéphane; Bayard, Sophie; Tattard, Philippe; Laraki, Yasmine; Capdevielle, Delphine (Frontiers in Psychiatry, 2023)
Objective: Decision-making capacity for treatment is impaired in schizophrenia but it remains unknown if schizophrenia affects distinct decision-making capacities differently.In this study, we assessed concomitantly two decision-making capacities (i.e., antipsychotic treatment and COVID-19 vaccination) in 27 schizophrenia patients. Sociodemographic variables, psychotic symptoms, global cognition and insight were also assessed.We found that among individuals incompetent to consent to antipsychotic treatment, onethird had preserved capacity to consent to vaccination. No significant associations between the two different decision-making capacities were found. Psychotic symptoms and cognition were associated with the capacity to consent to antipsychotic treatment and to vaccination, respectively.Clinicians should be aware that capacity to consent to treatment is not unidimensional and vary across domains in individuals with schizophrenia. Being incompetent regarding one treatment does not mean to be incompetent for another treatment in this clinical population.